Priming the primary motor cortex with transcranial direct current stimulation: Effect on learning the golf putt - Bisman Mangat; Luc Tremblay; Joyce L. Chen (PLoS ONE, 2025)
Background Priming the primary motor cortex (M1) with transcranial direct current stimulation (tDCS) prior to motor practice modulates post-synaptic activity, thereby impacting learning of a motor skill. This effect has been shown for the acquisition of simple motor skills. It is not clear whether priming tDCS can impact the learning/retention of a more naturalistic motor task. Objective/Hypothesis We investigated the effects of priming M1 with tDCS on the performance on a golf putting task. We hypothesized that participants who receive tDCS with the cathode over M1 (C-M1) would show better skill acquisition and retention performance, relative to participants who receive tDCS with the anode over M1 (A-M1) or sham tDCS. Methods Thirty-six participants were randomized into three groups: C-M1, A-M1, and sham tDCS. Participants received tDCS (1mA, 20 minutes) prior to practicing golf putting across two days. Performance (error) was measured for each putt. Participants returned on the third day for a retention test. Results After accounting for baseline performance, the C-M1 group performed significantly better compared to A-M1 [p = 0.02] and sham tDCS [p = 0.01] at the retention test. There was no difference in retention performance between A-M1 and sham tDCS. Conclusion Our findings partially support the Bienenstock-Cooper-Munro rule of metaplasticity. C-M1 tDCS priming enhanced motor learning, while A-M1 tDCS priming had no effect, relative to sham.